Abolition geography : essays towards liberation - Gilmore, Ruth Wilson; Bhandar, Brenna, 1973-; Toscano, Alberto (London : Verso, 2022)
"The first collection of writings from one of the foremost contemporary critical thinkers on racism, geography and incarceration."--
"Gathering together Ruth Wilson Gilmore's work from over three decades, Abolition Geography presents her singular contribution to the politics of abolition as theorist, researcher, and organizer, offering scholars and activists ways of seeing and doing to help navigate our turbulent present. Abolition Geography moves us away from explanations of mass incarceration and racist violence focused on uninterrupted histories of prejudice or the dull compulsion of neoliberal economics. Instead, Gilmore offers a geographical grasp of how contemporary racial capitalism operates through an 'anti-state state' that answers crises with the organized abandonment of people and environments deemed surplus to requirement. Gilmore escapes one-dimensional conceptions of what liberation demands, who demands liberation, or what indeed is to be abolished. Drawing on the lessons of grassroots organizing and internationalist imaginaries, Abolition Geography undoes the identification of abolition with mere decarceration, and reminds us that freedom is not a mere principle but a place."--Verso Books product page.
Includes bibliographical references and index.
Keywords: Prison abolition movements; Discrimination in criminal justice administration -- United States; Racism -- Political aspects; Crime and race; Human geography; Antislavery movements; Mouvements antiesclavagistes; Racisme -- Aspect politique; Antislavery movements; Human geography; Prison abolition movements; Racism -- Political aspects; United States -- Race relations; Cultural, ethnic & media studies; Essays; Essays